Screening strategies for identifying RNA- and ribonucleoprotein-targeted compounds. (September 2021) - Martin, William J.; Grandi, Paola; Marcia, Marco
Abstract : The past few years have witnessed important breakthroughs in the identification of compounds that specifically bind and regulate RNAs and in optimizing them for therapeutic use. Here, we review successful and unsuccessful approaches in screening for RNA-targeted small molecules. We discuss advantages and disadvantages of the different screening techniques and variables that affect the outcome of RNA-screening projects. We also highlight key challenges that hamper the development of quality RNA ligands, especially the still-low availability of RNA-specific compound libraries and the poor understanding of RNA structural dynamics. We conclude that the development of new RNA-targeting drugs would greatly benefit from integration of the power of high-throughput screening technologies with improved biochemical, structural, and computational characterization of RNA targets. Highlights: RNA molecules are emerging therapeutic targets, but the principles of best practice for RNA targeting are still being established. The identification of RNA-targeting small molecules involves screening novel compounds at high throughput, optimizing powerful mechanism-based assays, and developing ad hoc computational tools. An increasingly successful route to target RNA is to intervene in its 'life cycle' (biogenesis, modifications, cell localization, degradation) instead of or in addition to identifying compounds that bind RNA directly. A common pitfall is the development of high-affinity ligands that fail to induce the desired phenotypic effects. Careful dissection of successful screening projects helps to identify specific factors crucial for RNA-targeted screens. Areas of important consideration include target selection, compound libraries, the use of complementary assays, and compound optimization.